A high fatigue life rubber composite material and its preparation method and application

By introducing random copolymer structure of butanomine rubber into rubber composite materials and combining other components and processes, the problem of poor fatigue resistance of existing composite rubber materials is solved, significantly improving the fatigue life and crack resistance of the material.

CN115850814BActive Publication Date: 2025-03-21QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211531435.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-03-21
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

现有复合橡胶材料的抗疲劳性能较差,难以满足动态变形情况下的使用安全性和可靠性要求。

Method used

The butane rubber with a random copolymer structure catalyzed by an iron catalyst is used to prepare rubber composite materials with high fatigue life through specific kneading and glue removal processes.

Benefits of technology

It significantly improves the fatigue resistance of rubber composite materials, improves fatigue life, enhances the crack resistance and crack growth resistance of the material, and reduces the problems of uneven stress distribution of bending heat generation and stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003976179530000061
    Figure BDA0003976179530000061
  • Figure BDA0003976179530000071
    Figure BDA0003976179530000071
  • Figure BDA0003976179530000072
    Figure BDA0003976179530000072
Patent Text Reader

Abstract

A high fatigue life rubber composite material and its preparation method and application. The present invention belongs to the field of rubber materials and their preparation. The purpose of the present invention is to solve the technical problem that the existing composite rubber materials have poor fatigue resistance. The high fatigue life rubber composite material of the present invention is prepared from natural rubber, butadiene-butadiene rubber, plasticizer, reinforcing filler, activator, sulfur, accelerator and antioxidant, and the butadiene-butadiene rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side group contents is 40-60%. A high fatigue life rubber composite material of the present invention is used to prepare rubber products used in dynamic deformation conditions such as tires, rubber air springs, conveyor belts or sports shoe soles. The iron-based butadiene-butadiene rubber molecular chain used in the present invention has good flexibility and small hysteresis loss, which can effectively improve the fatigue life of the rubber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of rubber materials and preparation thereof, and in particular relates to a high fatigue life rubber composite material and a preparation method and application thereof. Background Art

[0002] The fatigue performance of rubber materials can be defined as the phenomenon that the physical and mechanical properties of materials decrease due to periodic deformation. Fatigue failure refers to the phenomenon that micro damage occurs on the surface or inside of the material under conditions below its breaking strength, and gradually develops into macro cracks and finally breaks, causing the product to lose its function.

[0003] Rubber products such as tires, rubber air springs, conveyor belts, and sports shoe soles are used under dynamic deformation conditions. In order to ensure the safety and reliability of rubber products and extend the service life of the products, it is extremely important to study the fatigue resistance of rubber materials. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem that the existing composite rubber material has poor fatigue resistance, and to provide a high fatigue life rubber composite material and a preparation method and application thereof.

[0005] A high fatigue life rubber composite material of the present invention is prepared from the following components by weight:

[0006] Natural rubber 40-90 parts;

[0007] 10-60 parts of butadiene-pentadiene rubber;

[0008] Plasticizer 0-40 parts;

[0009] 30-80 parts of reinforcing filler;

[0010] 2-9 parts of active agent;

[0011] 1-3 parts of sulfur;

[0012] 1-5 parts of accelerator;

[0013] 1 to 5 parts of antioxidant;

[0014] Butadiene-pentadiene rubber is a random copolymer obtained by catalysis of an iron-based catalyst, in which the sum of the ethylene and propylene side group contents is 40-60%.

[0015] It is further defined that the butadiene-pentadiene rubber is made from butadiene monomer and isoprene monomer in a molar ratio of (0.5-2):1, and has a molecular weight of 20-50w.

[0016] It is further defined that the butadiene-pentadiene rubber is composed of butadiene structural units and isoprene structural units, the molar content of 1,2-butadiene in the butadiene structural units is 60-80%, the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 20-40%, the molar content of 3,4-isoprene in the isoprene structural units is 20-30%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 70-80%.

[0017] It is further defined that the plasticizer is one or a mixture of several of naphthenic oil, aromatic oil and paraffin oil in any ratio.

[0018] It is further defined that the reinforcing filler is one of carbon black and white carbon black or a mixture of the two in any ratio.

[0019] It is further defined that the active agent is a mixture of stearic acid and zinc oxide.

[0020] It is further defined that the weight portion of zinc oxide in the active agent is 1-5 parts, and the weight portion of stearic acid is 0.5-5 parts.

[0021] It is further defined that the accelerator is one or a mixture of any ratio of sulfonamide accelerators, thiazole accelerators, thiuram accelerators and guanidine accelerators.

[0022] It is further defined that the antioxidant is a mixture of one or both of antioxidant 4020 and antioxidant RD in any ratio.

[0023] The preparation method of a high fatigue life rubber composite material of the present invention is carried out according to the following steps:

[0024] Step 1: Add natural rubber and butylene-pentadiene rubber to an internal mixer and mix for 60-90 seconds, then add an active agent and an antioxidant and mix for 60-90 seconds, then add half of the reinforcing filler and the plasticizer and mix for 120-150 seconds, then add the remaining reinforcing filler and continue mixing for 120-240 seconds, and then perform rubber removal to obtain a mixed rubber;

[0025] Step 2: Add sulfur and accelerator to the mixed rubber and mix for 120-180 seconds to obtain a rubber composite material with high fatigue life.

[0026] It is further defined that the debinding temperature in step 1 is ≤ 155°C.

[0027] It is further defined that the mixing temperature in step 1 is 90-155°C.

[0028] It is further defined that the mixing temperature in step 2 is 90-110°C.

[0029] The high fatigue life rubber composite material of the invention is used for preparing tires, rubber air springs, conveyor belts or sports shoe soles.

[0030] Compared with the prior art, the present invention has the following significant effects:

[0031] The present invention significantly improves the fatigue resistance of the rubber composite material by introducing the iron-based butadiene-pentadiene rubber with a random copolymer structure into the rubber system. The specific advantages are as follows:

[0032] 1) The iron-based butadiene-pentadiene rubber used in the present invention is a random copolymer. Compared with the block copolymer structure, the random copolymer has no crystal structure, so that the molecular chain of the butadiene-pentadiene rubber has better flexibility and less hysteresis loss, which can effectively improve the fatigue life of the rubber composite material.

[0033] 2) The tertiary carbon atom content in the structure of the butadiene-pentadiene rubber used in the present invention is high, which causes weak bond breakage during repeated flexural cracking. The carbon free radicals formed after the breakage can continue to cross-link or form a bonded rubber with carbon black, thereby improving the destruction and reconstruction capabilities of the network structure of the rubber composite material and having little effect on the energy storage and loss modulus; in addition, the weak electron-withdrawing side groups of the butadiene-pentadiene rubber reduce its crosslinking density, wherein the vinyl side groups can better improve the deformation ability of the molecular chain compared to the propylene side groups, thereby improving the crack resistance and crack growth resistance of the composite material.

[0034] 3) In the molecular chain of the iron-based butyl-pentene rubber used in the present invention, the content of vinyl and propylene side groups is 40%-60%. A certain content of side groups can reduce the degree of entanglement within and between molecular chains, and can increase the distance between molecular chains, so that the reinforcing filler and the molecular chain have a higher contact area. On the one hand, the bound rubber content in the rubber composite material is increased, and then the rubber composite material has the ability to resist higher stress during fatigue; on the other hand, the degree of dispersion of the reinforcing filler in the composite material is improved, which can better eliminate the problem of fatigue damage caused by stress concentration caused by uneven stress distribution of rubber during fatigue. However, with the increase of the side group content, the flexibility of the molecular chain continues to decrease. When the side group content exceeds 60%, the poor flexibility of the butyl-pentene rubber segment will bring about problems such as increased flexural heat generation and increased Mooney viscosity, which reduces the improvement effect of fatigue resistance life performance.

[0035] 4) The iron-based butadiene rubber used in the present invention has a relatively high content of 1,2-butadiene, and the vinyl side group has a small structural feature relative to the propenyl side group, thereby having a lower hysteresis heat generation effect, reducing the problem of aging flex cracking caused by the heat generated during the flexing process. In addition, the iron-based butadiene rubber used in the present invention also contains 3,4-isoprene with a molar content of 20%-30% and 1,4-isoprene with a molar content of 70%-80%. On the one hand, the contribution of the propenyl side group to the glass transition temperature of the composite material is greater than that of the vinyl group, so that under the action of dynamic strain, the molecular chain has no time to move, the relaxation effect is obvious, and the flex crack resistance performance is improved; on the other hand, the higher 1,4-isoprene structure content can well achieve the compatibility level with the natural rubber segment, so that the rubber composite material can give full play to the anti-fatigue characteristics of butadiene rubber on the basis of the excellent mechanical properties and fatigue properties of natural rubber, and the synergistic effect is obvious. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0038] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0039] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0040] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0041] Example 1: The formula composition of the high fatigue life rubber composite material of this example is listed in Table 1, and the performance test results are shown in Table 2;

[0042] The butadiene-vinyl rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side groups is 46.4%;

[0043] The butylene-vinyl rubber is prepared from butadiene monomer and isoprene monomer in a molar ratio of 1.5:1, and the molecular weight of the obtained butylene-vinyl rubber is 32.5w;

[0044] Butadiene-vinyl rubber is composed of butadiene structural units and isoprene structural units. The molar content of 1,2-butadiene in the butadiene structural units is 62%, and the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 38%. The molar content of 3,4-isoprene in the isoprene structural units is 23%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 77%.

[0045] The preparation method is carried out according to the following steps:

[0046] Step 1: Add natural rubber and butyl rubber to an internal mixer and mix at 95°C for 60 seconds, then add zinc oxide, stearic acid, antioxidant 4020 and antioxidant RD, mix for 75 seconds, then add half of the carbon black and cyclohexane oil and mix for 120 seconds, then add the remaining carbon black and continue mixing for 150 seconds, then perform debonding at a debonding temperature of 145°C to obtain a mixed rubber;

[0047] Step 2: Add sulfur and accelerator DM to the mixed rubber and mix them at a mixing temperature of 95° C. for 150 seconds to obtain a rubber composite material with a high fatigue life.

[0048] Example 2: The formula composition of the high fatigue life rubber composite material of this example is listed in Table 1, and the performance test results are shown in Table 2;

[0049] The butadiene-pentadiene rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side groups is 47%;

[0050] The butylene-vinyl rubber is prepared from butadiene monomer and isoprene monomer in a molar ratio of 1:1, and the molecular weight of the obtained butylene-vinyl rubber is 44.7w;

[0051] Butadiene-vinyl rubber is composed of butadiene structural units and isoprene structural units. The molar content of 1,2-butadiene in the butadiene structural units is 66%, and the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 34%. The molar content of 3,4-isoprene in the isoprene structural units is 28%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 72%.

[0052] The preparation method is carried out according to the following steps:

[0053] Step 1: Add natural rubber and butyl rubber to an internal mixer and mix at 90°C for 80 seconds, then add zinc oxide, stearic acid, antioxidant 4020 and antioxidant RD, mix for 60 seconds, then add half of the carbon black and cyclohexane oil and mix for 140 seconds, then add the remaining carbon black and continue mixing for 160 seconds, then perform debonding at a debonding temperature of 135°C to obtain a mixed rubber;

[0054] Step 2: Add sulfur and accelerator DM to the mixed rubber and mix them at a mixing temperature of 100° C. for 150 seconds to obtain a rubber composite material with a high fatigue life.

[0055] Example 3: The formula composition of the high fatigue life rubber composite material of this example is listed in Table 1, and the performance test results are shown in Table 2;

[0056] The butadiene-pentadiene rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side groups is 56.7%;

[0057] The butylene-vinyl rubber is prepared from butadiene monomer and isoprene monomer in a molar ratio of 2:1, and the molecular weight of the obtained butylene-vinyl rubber is 32.3w;

[0058] Butadiene-vinyl rubber is composed of butadiene structural units and isoprene structural units. The molar content of 1,2-butadiene in the butadiene structural units is 72%, and the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 28%. The molar content of 3,4-isoprene in the isoprene structural units is 26%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 74%.

[0059] The preparation method is carried out according to the following steps:

[0060] Step 1: Add natural rubber and butyl rubber to an internal mixer and mix at 100°C for 75 seconds, then add zinc oxide, stearic acid, antioxidant 4020 and antioxidant RD, mix for 90 seconds, then add half of the carbon black and cyclohexane oil and mix for 120 seconds, then add the remaining carbon black and continue mixing for 180 seconds, then perform debonding at a debonding temperature of 145°C to obtain a mixed rubber;

[0061] Step 2: Add sulfur and accelerator DM to the mixed rubber and mix them at a mixing temperature of 90° C. for 150 seconds to obtain a rubber composite material with a high fatigue life.

[0062] Example 4: The formula composition of the high fatigue life rubber composite material of this example is listed in Table 1, and the performance test results are shown in Table 2;

[0063] The butadiene-vinyl rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side groups is 48.5%;

[0064] The butadiene-vinyl rubber is prepared from butadiene monomer and isoprene monomer in a molar ratio of 1:1, and the molecular weight of the obtained butadiene-vinyl rubber is 36.3w;

[0065] Butadiene-vinyl rubber is composed of butadiene structural units and isoprene structural units. The molar content of 1,2-butadiene in the butadiene structural units is 70%, and the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 30%. The molar content of 3,4-isoprene in the isoprene structural units is 27%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 73%.

[0066] The preparation method is carried out according to the following steps:

[0067] Step 1: Add natural rubber and butyl rubber to an internal mixer and mix at 95°C for 90 seconds, then add zinc oxide, stearic acid, antioxidant 4020 and antioxidant RD, mix for 60 seconds, then add half of the carbon black and cyclohexane oil and mix for 140 seconds, then add the remaining carbon black and continue mixing for 220 seconds, then perform debonding at a debonding temperature of 135°C to obtain a mixed rubber;

[0068] Step 2: Add sulfur and accelerator DM to the mixed rubber and mix them at a mixing temperature of 95° C. for 150 seconds to obtain a rubber composite material with a high fatigue life.

[0069] Comparative Example 1: The formula composition of the rubber composite material of this embodiment is listed in Table 1, the preparation method is the same as that of Example 1, and the performance test results are shown in Table 2.

[0070] Comparative Example 2: The formulation composition of the rubber composite material of this embodiment is listed in Table 1, the preparation method is the same as that of Example 4, and the performance test results are shown in Table 2.

[0071] Comparative Example 3: The formulation of the rubber composite material of this embodiment is listed in Table 1, and the performance test results are shown in Table 2;

[0072] The butadiene-vinyl rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the ethylene and propylene side groups is 65.3%;

[0073] The butylene-vinyl rubber is prepared from butadiene monomer and isoprene monomer in a molar ratio of 2:1, and the molecular weight of the obtained butylene-vinyl rubber is 43.2w;

[0074] Butadiene-vinyl rubber is composed of butadiene structural units and isoprene structural units. The molar content of 1,2-butadiene in the butadiene structural units is 66%, and the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 34%. The molar content of 3,4-isoprene in the isoprene structural units is 64%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 36%.

[0075] The preparation method is the same as Example 2.

[0076] Table 1 Formulation of rubber composite materials

[0077]

[0078]

[0079] Table 2 Rubber composite material properties

[0080]

[0081] Note: The flexural fatigue test is tested in accordance with GB / T13934-2006; the flexural heat generation test is tested in accordance with GB1687-2016; the Payne effect test conditions are fixed temperature 60°C, frequency 1Hz, strain range 0.5-97%; the bonded rubber test is 0.5g of mixed rubber immersed in toluene solvent at room temperature for 72h, and then immersed for another 48h after changing the solvent; the glass transition temperature is the DMA test result, the test conditions are 3°C / min, frequency 10Hz, temperature -80-80°C.

[0082] Analysis of the data in Table 2 shows that when butadiene-vinyl rubber partially replaces natural rubber, the mechanical properties of the composite material are less affected due to the good compatibility between butadiene-vinyl rubber and natural rubber. When comparative example 3 changes the content of butadiene-vinyl rubber side groups, the blended vulcanized rubber shows two glass transition temperatures through DMA test, the compatibility between butadiene-vinyl rubber and natural rubber deteriorates, the mechanical strength of the composite material decreases, and the higher propylene side groups lead to higher flexural heat generation, while the effect on improving fatigue life is average.

[0083] By comparing and analyzing the examples 1-4 and the comparative example 1, under the reasonable structural design conditions of the butyl-pentene rubber, with the improvement of the proportion of the butyl-pentene rubber, the action force between the carbon black and the molecular chain of the composite material is increased (combined with the improvement of the content of the rubber and the reduction of the Payne effect), the bending heat generation performance of the composite material is reduced or substantially not affected, and the thermal oxidation aging mechanical property retention rate of the composite material is improved. At the same time, the crack resistance (first-level times) and crack growth resistance (sixth-level times) of the composite material can be improved well, thereby improving the fatigue life of the composite material. When the proportion of the butyl-pentene rubber exceeds 60 parts, the glass transition temperature of the composite material is reduced more, and the requirements of the outdoor environment for the glass transition temperature of the material cannot be better met.

[0084] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A high fatigue life rubber composite material, characterized in that: It is prepared from the following components by weight: Natural rubber 40-90 parts; 10-60 parts of butadiene-pentadiene rubber; Plasticizer 0-40 parts; 30-80 parts of reinforcing filler; 2-9 parts of active agent; 1-3 parts of sulfur; 1-5 parts of accelerator; 1 to 5 parts of antioxidant; The butadiene-vinyl rubber is a random copolymer obtained by catalysis of an iron-based catalyst, wherein the sum of the contents of ethylene and propylene side groups is 40-60%, the butadiene-vinyl rubber is prepared from butadiene monomers and isoprene monomers in a molar ratio of (0.5-2):1, and has a molecular weight of 20-50w. The butadiene-vinyl rubber consists of butadiene structural units and isoprene structural units, the molar content of 1,2-butadiene in the butadiene structural units is 60-80%, the sum of the molar contents of cis-1,4-butadiene and trans-1,4-butadiene is 20-40%, the molar content of 3,4-isoprene in the isoprene structural units is 20-30%, and the sum of the molar contents of cis-1,4-isoprene and trans-1,4-isoprene is 70-80%.

2. The high fatigue life rubber composite material according to claim 1, characterized in that: The plasticizer is a mixture of one or more of cyclohexane oil, aromatic oil, and paraffin oil; the reinforcing filler is a mixture of one or two of carbon black and white carbon black; the activator is a mixture of stearic acid and zinc oxide; the accelerator is a mixture of one or more of sulfonamide, thiazole, thiuram, and guanidine accelerators; and the antioxidant is a mixture of one or two of antioxidant 4020 and antioxidant RD.

3. The high fatigue life rubber composite material according to claim 2, characterized in that: The weight portion of zinc oxide in the active agent is 1-5 parts, and the weight portion of stearic acid is 0.5-5 parts.

4. The method for preparing the high fatigue life rubber composite material according to any one of claims 1 to 3, characterized in that: The method proceeds as follows: Step 1: Add natural rubber and butylene-pentadiene rubber to an internal mixer and mix for 60-90 seconds, then add an active agent and an antioxidant and mix for 60-90 seconds, then add half of the reinforcing filler and the plasticizer and mix for 120-150 seconds, then add the remaining reinforcing filler and continue mixing for 120-240 seconds, and then perform rubber removal to obtain a mixed rubber; Step 2: Add sulfur and accelerator to the mixed rubber and mix for 120-180 seconds to obtain a rubber composite material with high fatigue life.

5. The method according to claim 4, characterized in that In step 1, the debinding temperature is ≤155°C.

6. The method according to claim 4, characterized in that The mixing temperature in step 1 is 90-155°C.

7. The method according to claim 4, characterized in that The mixing temperature in step 2 is 90-110°C.

8. The high fatigue life rubber composite material according to any one of claims 1 to 3 is used for preparing tires, rubber air springs, conveyor belts or sports shoe soles.

Citation Information

Patent Citations

  • High-fatigue-life rubber belt and preparation method thereof

    CN109206678A

  • Rubber damping material with long fatigue life and preparation method of rubber damping material

    CN109400979A